From Brexit to Trump: Anthropology and the rise of nationalist populism - GUSTERSON, HUGH (American ethnologist, 2017)
Brexit and Donald Trump's election victory are symptoms of a new nationalist populism in western Europe and the United States. This political and ideological movement has arisen in reaction to reconfigurations of power, wealth, and identity that are endemic to global neoliberalism. In the United States, however, the media's dominant "blue-collar narrative" about Trump's victory simplifies the relationship between neoliberalism and nationalist populism by ignoring the role of the petty bourgeoisie and the wealthy in Trump's coalition. An anthropology of Trump requires ethnographies of communities largely shunned by anthropologists as well as reftexivity about the unintended role of universities in producing support for Trump.